Biocontrol efficacy of atoxigenic Aspergillus flavus strains against aflatoxin contamination in peanut field in Guangdong province, South China. Issue 2 (3rd April 2022) - Mamo, Firew Tafesse; Shang, Bo; Selvaraj, Jonathan Nimal; Zheng, Yongquan; Liu, Yang
ABSTRACT: Application of atoxigenic strains of Aspergillus flavus to soils is the most successful aflatoxin biological control approach. The objective of this study was to evaluate the efficacies of native non-aflatoxin producing (atoxigenic) strains as a biocontrol agent in peanut field in China. The competitive atoxigenic A. flavus strains (JS4, SI1and SXN) isolated from different crops, in China were used for field evaluation. The strains applied during the growing season (June – October, 2016) in the field at rate of 25 kg inoculum/hectare. The colonization of these biocontrol agents has been investigated and the population of A. flavus communities in soil were determined. The incidences of toxin producing (toxigenic) A. flavus strains and aflatoxin contamination in peanuts were also determined. Treated plots produced significant reductions in the incidence of toxigenic isolates of A. flavus in soil. However, the total fungal densities were not significantly different (p > 0.05) after treatments. Large percentage of aflatoxin reductions, ranging from 82.8% (SXN) up to 87.2% (JS4) were recorded in treated plots. Generally, the results suggest that the strategy can be used to control aflatoxin contamination and continuous evaluation should be done.